1988
DOI: 10.3354/dao005163
|View full text |Cite
|
Sign up to set email alerts
|

Paramoeba pemaquidensis (Sarcomastigophora: Paramoebidae) infestation of the gills of coho salmon Oncorhynchus kisutch reared in sea water

Abstract: Gill disease associated with Paramoeba pemaquidensis Page 1970 (Sarcomastigophora: Paramoebidae) infestations was observed in coho salmon Oncorhynchus lasutch reared in sea water Fish reared in net pens in Washington and in land-based tanks in California were affected. Approximately 25 O/ O mortality was observed in the net pens in 1985, and the disease recurred in 1986 and 1987. Amoeba infesting the gill surfaces elicited prominent epithelia1 hyperplasia. Typical of Paramoeba spp., the parasite had a Feulgen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
203
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 169 publications
(212 citation statements)
references
References 14 publications
8
203
1
Order By: Relevance
“…can infect gills and cause AGD in salmonids (Group 1) after KMnO 4 disinfection and with very low levels of culturable bacteria. Therefore, in agreement with other authors we have shown that the amoeba can be a primary pathogen and cause AGD in salmon (Kent et al 1988, Roubal et al 1989, Munday et al 1990, Dyková et al 1995, Adams & Nowak 2003. …”
supporting
confidence: 79%
See 2 more Smart Citations
“…can infect gills and cause AGD in salmonids (Group 1) after KMnO 4 disinfection and with very low levels of culturable bacteria. Therefore, in agreement with other authors we have shown that the amoeba can be a primary pathogen and cause AGD in salmon (Kent et al 1988, Roubal et al 1989, Munday et al 1990, Dyková et al 1995, Adams & Nowak 2003. …”
supporting
confidence: 79%
“…survival and growth, once it has gained access to salmon gills, has not been clearly identified. Previous researchers suggest that other infectious amoebae may feed on gill bacteria (Noble et al 1997) and perhaps attain bloom populations in the presence of abundant food organisms (Kent et al 1988). In vitro growth of trophozoites of a Platyamoeba strain isolated from the diseased gill tissues of cultured turbot increased considerably in the presence of Aeromonas hydrophila, Vibrio natriegens, Pseudomonas nautica and Escherichia coli (Paniagua et al 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amoebae present in the epithelium in very small numbers. Bacappeared as round, crescentic to irregularly shaped, teria were not seen on gills of the majority of affected pale, amphophilic organisms with a few cytoplasmic fish but a few small colonies of robust Gram-positive granules (Kent et al 1988, Roubal et al 1989) and were coccobacilli were found in the interlamellar spaces of present on the superficial epithelium, on the epithefish regardless of disease status. Small colonies of lium of the interlamellar spaces and in intraepithelial Gram-negative, fine, short to filamentous rods were cystic spaces.…”
Section: Histopathology Of Tissues Other Than Gillsmentioning
confidence: 99%
“…In recent years, the association of amoebiasis with epizootics and mortalities of aquatic organisms has emphasized our relative lack of knowledge about the pathogenesis, epizootiology, and ecology of these amoebae (Jones 1985, Kent et al 1988). Of some concern is the potential transmission of normally freeliving amoebae to marine organisms and their apparent switch to pathogenic forms in stressed hosts.…”
mentioning
confidence: 99%